PENGARUH KEPEMILIKAN INSTITUSIONAL, UKURAN PERUSAHAAN, PROFITABILITAS DAN RISIKO BISNIS TERHADAP KEBIJAKAN HUTANG PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2008-2012 - Mardiyati, Umi; Susanti, Susi; Ahmad, Gatot Nazir (Fakultas Ekonomi, Universitas Negeri Jakarta, 2014)
The purpose of this study is to know the effect of Institutional Ownership, Firm Size, Profitability, and Business Risk on Manufacture Firm Debt Policy Listed in Indonesia Stock Exchange. The sample using purposive sampling. The research model in this study employs panel data analysis with fixed effect approach. The empirical results show that institutional ownership and firm size have positive and significant effect on debt policy. ROA have negative significant effect on debt policy, but business risk have negative and not significant effecton debt policy. Simultaneous test showed that institutional ownership, firm size, profitability, and business risk effect the debt policy. Key words: Institutional Ownership, Firm Size, ROA, Business Risk, Debt Policy, Manufacture Firm